Assessing the Durability Behaviour of Cement Stabilized Soil Bricks in Kabale Municipality. - Muzahura, Ronald (Kabale University, 2025)
The construction industry in Uganda and across Africa is undergoing a significant transformation as stakeholders seek sustainable and cost-effective building materials. Traditional fired bricks, while widely used, pose environmental challenges due to deforestation and high energy consumption during production. In response, cement-stabilized soil bricks (CSSBs) have emerged as a promising alternative, combining local materials with cement to enhance durability and structural integrity. This research project focuses on assessing the durability behavior of CSSBs specifically in Kabale Municipality, a region characterized by unique climatic and soil conditions. The results for the compressive strength of CSSBs clearly indicate that increasing cement content enhances the compressive strength of CSSBs. The substantial jump in strength from 10% to 20% cement content highlights the critical role of cement in providing structural integrity. The findings align with the UNBS standards, which specify a minimum compressive strength of 3.5 MPa for CSSBs, confirming that bricks with 10% cement and above meet and exceed this requirement. The results for water absorption show a reduction in water absorption with increasing cement content is a critical finding, as lower water absorption rates correlate with enhanced durability and resistance to moisture-related degradation. The UNBS standard allows a maximum water absorption of 15% for CSSBs, and all tested samples with cement content of 10% or more fell well below this limit. The unstabilized bricks (0% cement) demonstrated significantly lower compressive strength and no water absorption capacity, highlighting the necessity of cement stabilization for enhancing the performance of soil bricks. In conclusion, the results suggest that a cement content of 10% to 20% provides an effective balance between compressive strength and water absorption, making these percentages suitable for producing durable CSSBs in the local context.